2019
DOI: 10.1108/ijpsm-01-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impact of management on public and private nurses in Bangladesh

Abstract: Purpose The purpose of this paper is to use conservation of resources (COR) theory as a lens for comparing the impact of line management on Bangladeshi public and private nurses’ perception of work harassment, well-being and turnover intentions where Anglo-American and European management models have been super-imposed on an existing different culture. Design/methodology/approach Survey data were collected from 317 Bangladeshi nurses’ (131 from the public sector and 186 from the private sector). Structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…One reason for the decline in their well-being is the use of management models that increase work harassment (Brunetto et al, 2016), in turn normalising overwork (Xerri et al, 2021). As stated, work harassment is a negative workplace act involving large numbers of frontline staff experiencing chronic levels of high work intensity coupled with increased accountability and red tape (Farr-Wharton et al, 2019). Farr-Wharton et al ( 2022) found evidence of work harassment for nurses across the United Kingdom and the United States, and Xerri et al (2019Xerri et al ( , 2021 found evidence of work harassment in Bangladeshi and U.S. healthcare SLBs.…”
Section: Factor 3: Work Harassmentmentioning
confidence: 99%
“…One reason for the decline in their well-being is the use of management models that increase work harassment (Brunetto et al, 2016), in turn normalising overwork (Xerri et al, 2021). As stated, work harassment is a negative workplace act involving large numbers of frontline staff experiencing chronic levels of high work intensity coupled with increased accountability and red tape (Farr-Wharton et al, 2019). Farr-Wharton et al ( 2022) found evidence of work harassment for nurses across the United Kingdom and the United States, and Xerri et al (2019Xerri et al ( , 2021 found evidence of work harassment in Bangladeshi and U.S. healthcare SLBs.…”
Section: Factor 3: Work Harassmentmentioning
confidence: 99%
“…Therefore, this study aimed to investigate the role of WPV on female nurses' TI in the context of a developing country like Bangladesh and address associated factors after a years of the COVID-19 pandemic. A prior study reported that workplace harassment and nurses' wellbeing were highly varied by public vs. private sector in Bangladesh [33]. Thus, our study also aimed to specify the factors of TI by public sector vs. private sector stratification.…”
Section: Introductionmentioning
confidence: 98%
“…We included emotional contagion in the model because HRM Thompson (2011), De Voorde et al (2016 and Ulrich et al (2016) identify significant limitations in the role of HRM as the employees' champion. Indeed, some scholars (Macky and Boxall, 2008;Thompson, 2011;Brunetto et al, 2015;Farr-Wharton et al, 2019;Xerri et al, 2019) argue that HRMboth in theory and practicehas been complicit in supporting senior management to peruse unsustainable efficiency goals, which negatively impacts employee well-being.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) in a quantitative analysis of 588 private sector nurses found evidence of work harassment working in the United Kingdom and USA, and Xerri et al (2019) in their quantitative analysis showed the impact of work harassment on 317 Bangladeshi nurses' well-being.…”
Section: Work Harassmentmentioning
confidence: 99%
See 1 more Smart Citation